The working conditions of the Maghreb temporary workers in the Huelva camps - Echajri Amhaouch, Ilhame (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2021)
There will be no development or human progress without real and effective equality of opportunities between men and women. Therefore, any action by the public authorities to ensure equality between the sexes will have a multiplier effect that will drive social and economic improvements at all levels, particularly benefiting the most unprotected women, among which foreign workers are undoubtedly. This article focuses on a collective concrete number of immigrant women, victims of harsh living and working conditions, as well as sometimes different degrees of sexual violence. I am referring to the workers, mainly of Maghreb nationality, who every year arrive in the fields of Huelva to work on the plantation and /or harvesting of strawberries, raspberries and blueberries. The dubious recruitment formula used will be analysed in particular, and how it contributes to the extreme occupational and vital precariousness suffered by these women.